The Role of Renewable Energy in Ensuring Energy Security of Supply and Reducing Energy-Related Import - Aslanturk, Oguzhan; Kıprızlı, Goktug (International Journal of Energy Economics and Policy, 2020)
After the industrial revolution, energy and its raw materials became vital for the economic growth and national security. Energy, which is essential in the production process as intermediate asset, plays a role in all stages from transportation to the production of final goods. Energy, which determines the international competitive power of the countries, must be available in a long-term way in an affordable and accessible manner for the economic growth of countries in micro- and macro-scale. The aim of this study, which adopts analytical method in this way, is to emphasize that the inclination of energy poor countries to renewable energy sources within the context of energy security of supply will reduce the dependence on outer sources and thus the potential added value of this transformation to these countries should not be ignored. Importing energy, which is one of the biggest expenditure items of energy poor countries, often emerge as large budget expenditure or current account deficit for these countries. In this context, it was emphasized that in addition to the economic losses caused by energy imports in a country’s budget, outer risks for energy security of supply have the potential to negatively affect the sustainability of economic activities. Furthermore, the study looks at renewable energy sources differently from the studies in the literature which mainly examine renewable energy within the context of climate change and its contributions to the climate change mitigation activities. Thus, it is argued that, with the renewable energy, countries will increase their energy diversity and prevent risks that threaten energy security of supply and income losses caused by energy imports and reduce their dependence on imported energy. Keywords: Energy Security of Supply, Energy Import Reduction, Renewable Energy JEL Classifications: F52, H60, Q42 DOI: https://doi.org/10.32479/ijeep.8414